BCL2 and miR-181a transcriptional alterations in umbilical-cord blood cells can be putative biomarkers for obesity - Marcondes, João Paulo de Castro [UNESP] (2018)
Several findings suggest that in utero stressor stimuli can alter fetal development by promoting transcriptional changes, and predisposing the neonate to diseases later in life. This study aimed to investigate whether a hyperglycemic environment in pregnant women with gestational diabetes mellitus (GDM) is able to cause fetal genetic alterations and predispose neonates to obesity. Transcriptional alteration of SIRT1, TP53 and BCL2 genes, miR-181a (a SIRT1 or BCL2 regulator) and telomere length were evaluated in placental and umbilical-cord blood cells. Healthy (HP; n = 20) and GDM (n = 20) pregnant women and their respective neonates were included in the study. Additionally, obese (n = 20) and eutrophic (n = 20) adults also participated as reference populations. Gene expression data showed down-regulation of BCL2 in umbilical-cord and peripheral blood cells from GDM neonates and obese adults, respectively. The miR-181a was down-regulated only in umbilical-cord blood cells of GDM neonates. Telomere length presented no significant difference. In conclusion, our study demonstrated that the GDM hyperglycemic intrauterine environment promotes transcriptional alterations in BCL2 and miR-181a in neonate umbilical-cord blood cells. Furthermore, both GDM neonates and obese subjects share the same transcriptional alteration in BCL2. Considering the relationship between obesity development and the functions regulated by these two genes, BCL2 and miR-181a could be adopted as potential biomarkers for childhood obesity. However, further study designs are recommended to confirm this hypothesis.